Genealogi Islam di Turki dan Kaitannya dengan Perkembangan Bahasa Arab - Gustia Tahir (Al-Hikmah Journal for Religious Studies, 2019)
Turki is considered as superpower state because of its strong military and strategic region. Turki has  very strong army which was so called Jenisseri corps that always keep its territory. Beside militery, Turki is a state with large number of moslem population in the world. Therefore Islam is a very important element in Turki, because most people of Turki are moslems. After Turki Usmani Kingdom was distructed, it was then ruled by Mustafa Kemal Attaturk who made the West as his state reference. Turki was then changed to be secular. However, Turki has significant roles in spreading Islam due to its large region from Asia, Africa to Europe. It makes Turki become plural state with multi-etnics, race, cultures even religion.  Relating to Arabic Development, Turki didn’t pay much attention to it, even it was deleted in Turkish school. Turki prefered to be called Western community to Arabian community.